2017
DOI: 10.1177/2059513117728201
|View full text |Cite
|
Sign up to set email alerts
|

Measuring coagulation in burns: an evidence-based systematic review

Abstract: Introduction:Dynamic monitoring of coagulation is important to predict both haemorrhagic and thrombotic complications and to guide blood product administration. Reducing blood loss and tailoring blood product administration may improve patient outcome and reduce mortality associated with transfusion. The current literature lacks a systematic, critical appraisal of current best evidence on which clinical decisions may be based.Objectives:Establishing the role of different coagulation markers in burn patients, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 35 publications
0
9
1
8
Order By: Relevance
“…Total bilirubin, which is one of the risk factors in burns 10 , showed a similar pattern with creatinine in our study. The PT is also a known predictor of mortality in trauma patients, but is not a good predictor in burn patients 11 ; however, the mean plot of PT (Fig. 1 ) in this study showed good differentiation between the two groups in both the manners.…”
Section: Discussioncontrasting
confidence: 69%
“…Total bilirubin, which is one of the risk factors in burns 10 , showed a similar pattern with creatinine in our study. The PT is also a known predictor of mortality in trauma patients, but is not a good predictor in burn patients 11 ; however, the mean plot of PT (Fig. 1 ) in this study showed good differentiation between the two groups in both the manners.…”
Section: Discussioncontrasting
confidence: 69%
“…ABIC occurs after 4 to 16 h in approximately 30-40% in patients with severe burns [110,113,115]. Previous studies defined that the ABIC based on INR is higher by 1.2 or 1.3, but laboratory markers, such as INR and aPTT, turned out to be unreliable indicators of coagulation in patients with severe burns [116].…”
Section: Acute Burn-induced Coagulopathymentioning
confidence: 99%
“…53 Laboratory tests of coagulation have proved to be poor predictors of coagulation in burn patients, whereas viscoelastic tests give better real-time indication of coagulopathy as discussed in a recent review. 54 Clot strength and microstructure decreases with progressive haemodilution, which is another risk of over-resuscitation. 55 Blood loss during excision of large burn eschar has the potential to exceed a blood volume, despite the current practice of using tumescent infiltration techniques.…”
Section: Bleeding and Transfusionmentioning
confidence: 99%